Disruptions in Rheumatology Care and the Rise of Telehealth in Response to the COVID‐19 Pandemic in a Community Practice–Based Network. Issue 8 (6th July 2021) - George, Michael D.; Danila, Maria I.; Watrous, Daniel; Reddy, Shanmugapriya; Alper, Jeffrey; Xie, Fenglong; Nowell, W. Benjamin; Kallich, Joel; Clinton, Cassie; Saag, Kenneth G.; Curtis, Jeffrey R.
Abstract : Objective: The effect of the COVID‐19 pandemic on community‐based rheumatology care and the use of telehealth is unclear. We undertook this study to investigate the impact of the pandemic on rheumatology care delivery in a large community practice–based network. Methods: Using a community practice–based rheumatologist network, we examined trends in in‐person versus telehealth visits versus canceled visits in 3 time periods: pre–COVID‐19, COVID‐19 transition (6 weeks beginning March 23, 2020), and post–COVID‐19 transition (May‐August). In the transition period, we compared patients who received in‐person care versus telehealth visits versus those who cancelled all visits. We used multivariable logistic regression to identify factors associated with canceled or telehealth visits. Results: Pre–COVID‐19, there were 7, 075 visits/week among 60, 002 unique rheumatology patients cared for by ~300 providers practicing in 92 offices. This number decreased substantially (24.6% reduction) during the COVID‐19 transition period for in‐person visits but rebounded to pre–COVID‐19 levels during the post–COVID‐19 transition. There were almost no telehealth visits pre–COVID‐19, but telehealth increased substantially during the COVID‐19 transition (41.4% of all follow‐up visits) and slightly decreased during the post–COVID‐19 transition (27.7% of visits). Older age, female sex, Black or Hispanic race/ethnicity, lower socioeconomic status, and rural residence were associated with a greater likelihood of canceling visits. Most factors were also associated with a lower likelihood of having telehealth versus in‐office visits. Patients living further from the rheumatologists' office were more likely to use telehealth. Conclusion: COVID‐19 led to large disruptions in rheumatology care; these disruptions were only partially offset by increases in telehealth use and disproportionately affected racial/ethnic minorities and patients with lower socioeconomic status. During the COVID‐19 era, telehealth continues to be an important part of rheumatology practice, but disparities in access to care exist for some vulnerable groups.